Computer Self- Efficacy and Use of Cloud Computing for Personal Information Management among Undergraduate Students in a Nigerian University (2024)
This study investigated self-efficacy and use of cloud computing for personal information management among undergraduate students in Nigerian university. The descriptive survey research design was adopted for the study. The population of the study consists of all undergraduates in University of Ibadan, Nigeria. The study adopted a multistage sampling technique. The sample size for this study was 173 undergraduates. A structured questionnaire was the research instrument used for this study. Results was analysed using percentages, Mean and Standard Deviation. Findings revealed that the level of computer self-efficacy of undergraduates was very high (Mean=3.33). It was also revealed that most of the respondents 157 (91.3%) indicated to have used Google cloud platform (Gmail. Google Docs, Google Drive e.t.c), Furthermore, it was revealed that majority of the respondents, 113 (65.7%) were daily users of Google cloud. It was revealed that majority of the respondents agreed that slow data entry and slow downloading in database format rated as major challenge of the use of cloud computing for personal information management by the undergraduates. The study concluded that the use of cloud computing for personal information management by undergraduates is not only important for the building of their academic activities, but could also add value to their social relationship if deployed properly. It is therefore recommended that they should expand their scope beyond Google cloud platform in which majority of them are used to.